Recent progress, mechanisms, and perspectives for crystal and interface chemistry applying to the Zn metal anodes in aqueous zinc‐ion batteries. Issue 2 (28th April 2022) - Zhang, Zhengchunyu; Xi, Baojuan; Ma, Xiaojian; Chen, Weihua; Feng, Jinkui; Xiong, Shenglin
Abstract : Based on the crystal chemistry and interface chemistry, we organize this review to look back and put forward the design around the substrate, electrolyte, and their interface. These key points mainly pay close attention to inhibit dendritic growth and side reactions, then present the potential prospects for future work in this direction. It is foreseeable that this overview as a roadmap could realize accurate control of homogeneous Zn deposition and guide the construction of zinc batteries with high performance and reversibility.